Kritische Kreativität Perspektiven auf Arbeit, Bildung, Lifestyle und Kunst - Kannler, Kim; Klug, Valeska; Petzold, Kristina; Schaaf, Franziska (Kulturen der Gesellschaft, 2019)
Creativity - once the core demand of (artistic) social critique - today seems to be no more than an omnipresent social imperative. Their emancipatory potential became playful in favor of strategic exploitation by politics and economy, so the general reproach. Against this background, the volume addresses the multifaceted relationship between creativity and criticism. To this end, he brings together contributions from various research disciplines, artistic and activist practices along the central questions: How can the concept of creativity be criticized and (how) can its original critical potential be reactivated?